2020
DOI: 10.3390/ijerph17186714
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Active Video Games’ Energy Expenditure in Children with Overweight and Obesity and Differences by Gender

Abstract: (1) Background: Childhood obesity has become a main global health problem and active video games (AVG) could be used to increase energy expenditure. The aim of this study was to investigate the energy expenditure during an AVG intervention combined with exercise, differentiating by gender. (2) Methods: A total of 45 children with overweight or obesity (19 girls) performed an AVG intervention combined with exercise. The AVG used were the Xbox Kinect, Nintendo Wii, dance mats, BKOOL cycling simulator, and Ninten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 61 publications
(116 reference statements)
1
14
0
3
Order By: Relevance
“…Additionally, the children in the present study with the highest relative VO 2max would be classified into the low category (2.5–15.9%) for girls and boys aged 9–11 years without obesity. Similar results were found when VO 2max relative to lean mass, a measure that is not confounded by body adiposity [ 27 ], was considered. These results confirm that all study individuals had what is commonly defined as low CRF [ 34 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Additionally, the children in the present study with the highest relative VO 2max would be classified into the low category (2.5–15.9%) for girls and boys aged 9–11 years without obesity. Similar results were found when VO 2max relative to lean mass, a measure that is not confounded by body adiposity [ 27 ], was considered. These results confirm that all study individuals had what is commonly defined as low CRF [ 34 ].…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, these noteworthy differences in body composition could be attributable to the higher proportion of boys in Tanner stage 2, while more girls were in Tanner stage 1. In a previous study with part of the present sample, we found that boys who performed an active video game intervention combined with multi-component exercise had higher energy expenditure (5.68 vs. 4.66 kcal/min) than girls performing the same intervention [ 27 ].…”
Section: Discussionmentioning
confidence: 92%
“…The player's movements are detected through a Pilates ring (Ring-Con ® ) and a strap with a controller (Joy-Con ® ) that is fixed on the left leg. A recent study [32] found that the energy consumption of this video game is higher than that required by other exergames such as Wii Fit or Kinect Adventures.…”
Section: Wii Nintendo ®mentioning
confidence: 82%
“…Active-video games (AVG) have been proposed as a good alternative aiming to motivate those (young or not) who find sport less interesting, partly due to their body composition, poor performance or low motor skills. Scientific literature has shown the potential of AVG to increase the energy expenditure and to replace sedentary behaviors by promoting light-to-moderate PA [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Although some studies have reported the benefits of AVG on body composition [ 35 ], CRF [ 36 ], and motor competence [ 37 , 38 ], the effects of AVG on health-related physical fitness need further investigation because of the importance it can have for their present and future health.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore necessary to ascertain the potential of AVG for improving health in children and adolescents with healthy weight and for promoting a healthier lifestyle. As well, this update of the evidence is necessary as AVGs have been updated, offering more and more possibilities and increasing the physical demands in exercise sessions through AVG [ 34 ]. Consequently, this systematic review aims to identify and critically appraise current research results from the data obtained and to pool the results of published studies in a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%